2018
DOI: 10.1111/psyp.13275
|View full text |Cite
|
Sign up to set email alerts
|

Motivation alters implicit temporal attention through sustained and transient mechanisms: A behavioral and pupillometric study

Abstract: Temporal expectations aid performance by allowing the optimization of attentional readiness at moment of highest target probability. Reward enhances cognitive performance through its action on preparatory and reactive attentional processes. To elucidate how motivation interacts with mechanisms of implicit temporal attention, we studied healthy young adult participants (N = 73) performing a sustained attention task with simultaneous pupillometric recording, under different reward conditions (baseline: 0 c; rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…Such control mechanisms may serve to maintain higher levels of arousal/alertness throughout the waiting period, and/or by reactively mobilising compensatory resources whenever targets appear at moments of low readiness (i.e. short FPs; Massar et al., 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such control mechanisms may serve to maintain higher levels of arousal/alertness throughout the waiting period, and/or by reactively mobilising compensatory resources whenever targets appear at moments of low readiness (i.e. short FPs; Massar et al., 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…This has further implications on how the FP-effect is influenced by the history of FPs in preceding trials (a phenomenon called the sequential effect). Previous research has shown that the sequential effect is affected by SD (Kong et al, 2015) and by motivation (Massar et al, 2018a). The current task structure did not provide a sufficient number of trials to perform a fine-grained analysis on the sequential effect, and was not designed to arbitrate between the different theoretical accounts.…”
Section: Methods Smentioning
confidence: 99%
See 1 more Smart Citation
“…amounting to a total of 16 probes per foreperiod duration. Each task run contained Power analysis based on recent studies from our lab using the same PVT task as the 1 current study indicated that behavioral foreperiod effects are robust (partial-h 2 : 0.705-0.817) 2 (Massar et al, 2018;Sasmita et al, 2018), and a sample sizes of N = 6 to N = 8 would be 3 sufficient to detect these effects with power = 90% and alpha = .05. However, no prior 4 studies have examined the effect of foreperiod duration on mind wandering.…”
Section: Psychomotor Vigilance Task 12mentioning
confidence: 96%
“…be enhanced by the expectation of monetary rewards. Enhanced reactive control (Boehler, Schevernels, Hopf, Stoppel, & Krebs, 2014;Engelmann & Pessoa, 2007;Massar, Sasmita, Lim, & Chee, 2018) and greater attentional flexibility (Shen & Chun, 2011) are two potential additional benefits of anticipating reward. The reorienting of attention involves the disengagement and updating of original goal representations, and is essential for resolving cue-target incongruence.…”
Section: Introductionmentioning
confidence: 99%